2021
DOI: 10.3389/fendo.2021.621221
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of Inner Cell Mass Is the Strongest Predictor of Live Birth After a Frozen-Thawed Single Embryo Transfer

Abstract: BackgroundThe scoring system for human blastocysts is traditionally based on morphology; however, there are controversies on the effect of morphology parameters on pregnancy outcomes. The aim of this study is to evaluate the predicting value of each morphology parameter on pregnancy outcomes in a setting of single embryo transfer.MethodsThis is a retrospective cohort study on patients undergoing frozen-thawed single blastocyst transfer at our center, between Jan. 2009 and Dec. 2018. A total of 10,482 cycles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Embryo vitrification and warming were performed as previously described [ 20 ]. The embryos were vitrified within 2 h after scoring.…”
Section: Methodsmentioning
confidence: 99%
“…Embryo vitrification and warming were performed as previously described [ 20 ]. The embryos were vitrified within 2 h after scoring.…”
Section: Methodsmentioning
confidence: 99%
“…Inner cell mass and trophectoderm populations at the blastocyst stage are predictive of pregnancy and live birth outcomes [ 31 33 ]. In this study, we showed no impact on the ICM or total cell number for blastocysts exposed to the blue, green, and yellow wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with various other studies. A recent report from Ai et al (2021) evaluated the association of the morphological parameters in frozen SETs and found ICM grade was a stronger predictor of live birth ( Ai et al, 2021 ). Their classification of blastocysts and the conclusions were similar to the current study and may support our findings.…”
Section: Discussionmentioning
confidence: 99%